A Quasi-Experimental Evaluation of the Lifelong Links Intervention for Reducing Homelessness amongst Care Leavers. - Sanders, Michael; Hirneis, Vanessa; Picker, Vanessa (British Journal of Social Work, 2024)
Despite the fact that care leavers are at significantly higher risk of homelessness than their peers who have not experienced care, there is a paucity of information on evidence-based interventions to address this risk. Lifelong Links is a program developed and delivered by the Family Rights Group in England. The intervention aims to ensure that a child in care has a positive support network around them to help during their time in care and into adulthood. In this article, we analyse the outcomes of a quasi-experimental evaluation of the Lifelong Links program. Specifically, we make use of a combination of coarsened exact matching, and a triple-differences approach (or difference in difference in differences analysis). Results of our analyses show that Lifelong Links is associated with a reduction in the risk of becoming homeless for care leavers aged eighteen to twenty in the years following its implementation. Our most robust model showed a reduction of around 10 per cent in the risk of a young care leaver being deemed at risk of, or experiencing homelessness, suggesting that improving ties between young people in care and their birth families (and/or building other sources of support) could have beneficial impacts on housing outcomes into adulthood.